Program MULDER -- a tool for extracting torsion angles from NMR data - Padrta, Petr; Sklenár, Vladimír (Journal of biomolecular NMR, 2002)
MULDER (Mostly UniversaL Dihedral angle ExtractoR) is a program for extraction of torsion angle information from NMR data. Currently, it can analyze two types of input data: The torsion angle data, where several (3)J-coupling constants and/or interatomic distances are combined in order to reduce the torsion angle ambiguity arising from solving the isolated Karplus (or distance) equation, and the sugar pucker data, where the dynamics of five-membered sugar rings is evaluated by postprocessing the results calculated from (3)J((HH)) coupling constants by program PSEUROT. Program MULDER can be used either as an alternative to r-MD programs in situations where only specific structural features are studied, or as a preparatory tool in connection with full r-MD structure calculation for extraction of unambiguous torsion angle restraints.
Keywords: Software; software; DNA; Nucleic Acid Conformation; sekvence nukleotidů; Base Sequence; Deoxyribose; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; konformace nukleové kyseliny; deoxyribosa